CD4+ and CD8+ T cells play a central role in a HDM driven model of allergic asthma. Issue 1 (December 2016) - Raemdonck, Kristof; Baker, Katie; Dale, Nicole; Dubuis, Eric; Shala, Fisnik; Belvisi, Maria; Birrell, Mark
Abstract Background The incidence of asthma is increasing at an alarming rate and while the current available therapies are effective in the majority of patients they fail to adequately control symptoms at the more severe end of the disease spectrum. In the search to understand disease pathogenesis and find effective therapies animal models are often employed. As exposure to house dust mite (HDM) has a causative link, it is thought of as the allergen of choice for modelling asthma. The objective was to develop a HDM driven model of asthmatic sensitisation and characterise the role of key allergic effector cells/mediators. Methods Mice were sensitised with low doses of HDM and then subsequently challenged. Cellular inflammation, IgE and airway responsiveness (AHR) was assessed in wild type mice or CD4+ /CD8+ T cells, B cells or IgE knock out mice. Results Only those mice sensitised with HDM responded to subsequent low dose topical challenge. Similar to the classical ovalbumin model, there was no requirement for systemic alum sensitisation. Characterisation of the role of effector cells demonstrated that the allergic cellular inflammation and AHR was dependent on CD4+ and CD8+ T cells but not B cells or IgE. Finally, we show that this model, unlike the classic OVA model, appears to be resistant to developing tolerance. Conclusions This CD4+ /CD8+ T cell dependent, HDM driven model of allergic asthma exhibits key features of asthma. Furthermore, we suggest that the ability to repeat challenge with HDM means this model is amenable to studies exploring the effect of therapeutic dosing in chronic, established disease.